PENERAPAN METODE PEER TEACHING DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA - Ni Ketut Erawati; Agung Ari Sarasmita Anggreni; I Dewa Putu Sarjana (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
This research aims to improve students' understanding of mathematical concepts in mathematics learning with Pythagorean theorem material using the peer teaching method. This type of research is classroom action research with the research subjects being class VIII B students of SMP Negeri 3 Tabanan. This research was carried out in two cycles, with each cycle consisting of planning, action/implementation, observation and reflection stages. Data collection was carried out through tests of understanding mathematical concepts in the form of essays which were then analyzed quantitatively descriptively to determine the classification of learning activities in each cycle. The indicator of success in this research is the percentage of students' mathematical concept understanding test results in the high category. Based on research, it is known that there was an increase in students' understanding of mathematical concepts based on the results of implementation in cycle I, namely 68% which was in the sufficient category, then increased in cycle II to 80% which was in the high category. Based on the research results, it can be concluded that implementing learning using the peer teaching method can improve class students' understanding of mathematical concepts.